Implementation of PBL Model with Differentiated Learning to Improve Students' Motivation and Cognitive Learning Outcomes on Evolution Material - Zulfa Samawati; Fida Rachmadiarti; Dwi Emawati Susananingsih (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Each child has their uniqueness and the necessity to choose the correct learning technique so that it can fit all students' demands through differentiated learning by partnering with problem-based learning models to boost students' learning motivation and learning outcomes. This research is Class Action Research, which tries to determine the improvement of learning implementation on students' learning motivation and learning outcomes. The subjects of this study were all students of class XI A2.5 SMA Negeri 1 Krian totaling 35 students. Data collection was carried out using observation, questionnaire, and test procedures, with instruments in the form of observation sheets of learning differentiation with problem-based learning (PBL) models, questionnaire sheets of learning motivation, and learning outcomes test sheets. The results showed that the average learning implementation score in cycle I was 76% with an excellent category, whereas in cycle II it was 93% with a very good category. Student learning motivation before participating in the learning process was in the low category with an average score of 52.93% and after participating in the learning process, the average score of student learning motivation climbed to 76.32 in cycle I with a moderate motivated category and further climbed by 88.55% in the motivated category in cycle II. Students' cognitive learning outcomes in cycle I earned a gain score of 0.54 with a medium category, and in cycle II obtained a gain score of 0.84 with a high category. Based on the results of the study, it can be inferred that there is an increase in motivation and cognitive learning outcomes of students through the implementation of the differentiated learning PBL model on material about evolution.